Potensi Pengelolaan Lingkungan Perdesaan Berbasis Wisata - Sri Ratna Wulan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Tourism-based rural environmental management is one strategy to support the Indonesian government's policies to improve the non-agricultural economy and preserve rural areas. Each region has unique and different potential to be developed into a sustainable tourism area. This research aims to identify and analyze the potential for tourism-based rural environmental management in Cikole Village. The method used in this research is a qualitative and quantitative method with a dominant less dominant model with data collection techniques through interviews, field observations and literature studies. The research results show that Cikole Village has various environmental potentials that can be developed into a sustainable tourist destination. This potential is agro-tourism potential, natural tourism potential based on eco-tourism (forest tourism) and geo-tourism potential. Proper management of this potential will not only improve the local economy, but also preserve the rural environment.